Bio-Mirror project for public bio-data distribution - Gilbert, Donald G.; Ugawa, Yoshihiro; Buchhorn, Markus; Wee, Tan Tin; Mizushima, Akira; Kim, Hyun Chul; Chon, Kilnam; Weon, Seyeon; Ma, Juncai; Ichiyanagi, Yoshihiro; Liou, Der Ming; Keretho, Somnuk; et al. (Oxford University Press, 2004)
Timely worldwide distribution of biosequence and bioinformatics data depends on high performance networking and advances in Internet transport methods. The Bio-Mirror project focuses on providing up-to-date distribution of this rapidly growing and changing data. It offers FTP, Web and Rsync access to many high-volume databanks from several sites around the world. Experiments with data grids and other methods offer future improvements in biology data distribution. © Oxford University Press 2004; all rights reserved.